Genotypic detection of rifampicin and isoniazid resistant Mycobacterium tuberculosis strains by DNA sequencing: a randomized trial - El mashad Noha; Zaghloul Mohammad; El-Ghaffar Hassan; Abdelaal Amina; Badran Ehab; Fathy Amal (BMC, 2009)
Abstract Correction to Genotypic detection of rifampicin and isoniazid resistant Mycobacterium tuberculosis strains by DNA sequencing: a randomized trial Amina Abdelaal, Hassan Abd El-Ghaffar, Mohammad Hosam Eldeen Zaghloul, Noha El mashad, Ehab Badran, Amal Fathy Annals of Clinical Microbiology and Antimicrobials 2009, 8:4 (30 January 2009)